Brassinosteroids a class of plant hormone - Hayat, Shamsul; Ahmad, Aqil; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
Brassinosteroids (BRs) comprise a specific class of low-abundance plant steroids of ubiquitous occurrence in plants. This group of plant steroids includes more than 70 compounds that show structural similarities to insect, animal and human steroid hormones. Molecular genetic analysis of mutants defective in BRs biosynthesis or response revealed that BRs are essential for normal plant growth and development. These findings, together with the ubiquitous occurrence of BRs in plants and their highly effective elicitation of several responses have led to the recognition of BRs as a new class of plant hormones. The first BR, brassinolide, was identified in 1979 from pollen of Brassica napus. Since then, several practical applications for BRs, especially in agriculture, have been reported, tough, the high production cost of these natural plant steroids has hampered initiatives for their wide commercial use. However, the increasing availability of affordable commercial formulations produced in Japan, Russia, Belarus, China and India has open new perspectives for the wider commercial use of BRs. In this book BRs structure, signaling, biosynthesis, along with more recently proposed practical uses as well as proteomics study in regulation of brassinosteroids will be discussed. In one chapter possible medical application will also be described. The regular use of BRs in agriculture is expected to effectively contribute to increase food supply and consequently reduce hungry, which is of especial interest for undeveloped and developing countries. Finally, the medical application of the anticancer, antiviral and anti-inflammatory activity of BRs will significantly contribute to improve human wellness. Current work on brassinosteroids is somewhat diffuse; therefore, it was considered prudent to draw our current knowledge together into one volume. This book is not intended to serve as an encyclopedic review of the subject. However, the various chapters incorporate both theoretical and practical aspects and may serve as baseline information for future research through which significant development is possible. This book includes contributions from various experts worldwide. This work will facilitate a ready reference of current subject matter to students and researchers alike
Foreword -- Preface -- 1. Brassinosteroids-occurrence and chemical structures in plants, Andrzej Bajguz -- 2. Regulatory mechanism of brassinosteroid signaling in plants, M.-C. Codreanu and E. Russinova -- 3. Regulation of brassinosteroid metabolism, L. Hategan, B. Godza and M. Szekeres -- 4. Brassinosteroid signaling in rice, H. Nakagawa, A. Tanaka and M. Mori -- 5. Brassinosteroids and light - regulatory factors of growth and development of plants, I. F. Golovatskaya -- 6. Brassinosteroids and photosynthesis -- D. Holá -- 7. Physiological effects related to brassinosteroid application in plants, M.M.A. Gomes -- 8. Genomic and non-genomic events involved in the brassinosteroid promoted plant cell growth, A.B.Pereira-Netto -- 9. Role of brassinosteroids on horticultural crops, Y.Y.Kang and S.R.Guo -- 10. Brassinosteroid action and its relation with heat stress mechanisms in plants, L.M.Mazorra -- 11. Potective effects of brassinosteroids against herbicides, R. Piñol, E. Simón -- 12. Brassinosteroids: under biotic stress, Shamsul Hayat, Mohammad Irfan, Aqil Ahmad -- 13. The significance of ethanol as a hormone solvent in experiments on the physiological activity of brassinosteroids, Anna Janeczko -- 14. Immunoassays of brassinosteroids, V.A. Khripach, V.N.Zhabinskii, R.P. Litvinovskaya -- 15. Transcriptomics and proteomics study in regulation of brassinosteroids, H. F. Juan -- 16. Brassinosteroids for phytoremediation application, M. Barbafieri, E. Tassi -- 17. Prospects of brassinosteroids in medicinal applications, R. Bhardwaj, N. Arora, P. Uppal, I. Sharma, M.K. Kanwar -- Index
Title from title screen (viewed October 9, 2023)
Electronic reproduction
Keywords: Brassinosteroids